Sa majesté des Mouches et les bienheureux de la désolation
At first sight, Golding's Lord of the Flies and Bazin's Les Bienheureux de la Désolation would seem to be at opposite poles. In Bazin's work the inhabitants of Tristan da Cunha are evacuated to England to escape a volcanic eruption; Golding, by contrast, has a group of British schoolchildren stranded on an uninhabited island after being caught up in a global conflict. And whereas the latter revert to a primitive state by choosing leaders who adopt postures of mimetic rivalry, the Tristan islanders remain true to an egalitarian tradition that frowns on any open display of antagonism. In the event, however, it is precisely the children's emulation of their English model that results in their breaking away from it by forming competing groups and eliminating one of their number as a scapegoat, while it is the evacuees' commitment to a different model that leads them to reject anything that compromises an identity which, though highly distinctive in appearance, is in point of fact wholly mimetic.31 janvier 2018